Systematic Review of Reading Proficiency among Preschool Pupils Using PRISMA - Idris, Mariam Oluwatoyin; Che Mustafa, Mazlina; Wong, Kung-Teck; Hunpegan, Hendeweh Dorcas; Ismail, AbdulFatai Olohunfunmi (Asian Journal of Assessment in Teaching and Learning, 2024)
The mastery of reading and writing plays a pivotal role in an individual’s personal growth and is intrinsically linked to the acquisition of listening, speaking, reading, and writing skills—a critical facet of a child’s language development. This study conducts a systematic review of reading strategies utilized in promoting reading proficiency among preschoolers. The study meticulously explores reputable databases, including Google Scholar, Web of Science, and Scopus for reliable research papers. The review followed PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. This search yielded a total of 63 relevant articles published between 2008 and 2022. Following an in-depth assessment, 22 articles were identified and selected as most pertinent to the study’s objectives. The findings of this systematic review indicate that various reading strategy approaches, including Montessori, pedagogical, e-book, and child-centered methods, wield a positive impact on children’s reading skills. Notably, these approaches contribute significantly to decoding, fluency, and comprehension abilities among preschool learners. The implications of these findings underscore the potential for educators to employ these strategies effectively in preschool environments, fostering the development of young children’s reading skills.